Seasonal influenza vaccination delivery through community pharmacists in England: evaluation of the London pilot. Issue 2 (16th February 2016) - Atkins, Katherine; van Hoek, Albert Jan; Watson, Conall; Baguelin, Marc; Choga, Lethiwe; Patel, Anika; Raj, Thara; Jit, Mark; Griffiths, Ulla
Abstract : Objective: To evaluate the effectiveness and cost of the pan-London pharmacy initiative, a programme that allows administration of seasonal influenza vaccination to eligible patients at pharmacies. Design: We analysed 2013–2015 data on vaccination uptake in pharmacies via the Sonar reporting system, and the total vaccination uptake via 2011–2015 ImmForm general practitioner (GP) reporting system data. We conducted an online survey of London pharmacists who participate in the programme to assess time use data, vaccine choice, investment costs and opinions about the programme. We conducted an online survey of London GPs to assess vaccine choice of vaccine and opinions about the pharmacy vaccine delivery programme. Setting: All London boroughs. Participants: London-based GPs, and pharmacies that currently offer seasonal flu vaccination. Interventions: Not applicable. Main outcome measures: Comparison of annual vaccine uptake in London across risk groups from years before pharmacy vaccination introduction to after pharmacy vaccination introduction. Completeness of vaccine uptake reporting data. Cost to the National Health Service (NHS) of flu vaccine delivery at pharmacies with that at GPs. Cost to pharmacists of flu delivery. Opinions of pharmacists and GPs regarding the flu vaccine pharmacy initiative. Results: No significant change in the uptake of seasonal vaccination in any of the risk groups as a result of the pharmacy initiative. While on average a pharmacy-administered flu vaccine dose costs the NHS up to £2.35 less than a dose administered at a GP, a comparison of the 2 recording systems suggests there is substantial loss of data. Conclusions: Flu vaccine delivery through pharmacies shows potential for improving convenience for vaccine recipients. However, there is no evidence that vaccination uptake increases and the use of 2 separate recording systems leads to time-consuming data entry and missing vaccine record data.